Role of general practitioner in the management of acute myocardial infarction (Medical Journal of Indonesia, 2005)
Acute myocardial infarction (AMI) has been the leading cause of death in Western countries, as well as in Indonesia. Delay in diagnosis and incorrect early management often result in failure of thrombolytic reperfusion. General practitioner (GP) as the primary care, needs to be equipped with the ability to diagnose and moreover to manage AMI. A case of fail thrombolytic management in a 47 years old man after seven hours of angina typical chest pain, after previously managed by GP, is being reported. (Med J Indones 2005; 14:249-52)